Cardiopulmonary Bypass–Induced Inflammation and Myocardial Ischemia and Reperfusion Injury Stimulates Accumulation of Soluble MER*. Issue 9 (September 2021) - Becker, Amanda C.; Lantz, Connor W.; Forbess, Joseph M.; Epting, Conrad L.; Thorp, Edward B.
Abstract : Objectives: Soluble MER has emerged as a potential biomarker for delayed resolution of inflammation after myocardial injury and a therapeutic target to reduce cardiac-related morbidity and mortality in adults. The significance of soluble MER in pediatric populations, however, is unclear. We sought to investigate if soluble MER concentrations change in response to myocardial ischemia and reperfusion injury in pediatric patients. In parallel, we also sought to investigate for correlations between the change in soluble MER concentration and specific patient, bypass, and postoperative data. Design: We quantified the change in plasma soluble MER concentration post- compared with precardiopulmonary bypass for each patient in a cohort of pediatric patients. Linear regression, correlation coefficients, and t tests were used to compare innate patient characteristics (i.e., sex, age, cyanotic vs acyanotic cardiac lesion), cardiac bypass data (i.e., total cardiac bypass time, total aortic cross-clamp time, perioperative steroid administration), and postcardiac bypass data (total postoperative ventilator days, total postoperative vasoactive medication days, and total postoperative ICU days) with change in soluble MER concentrations. Setting: Whole blood samples were obtained intraoperatively at a single tertiary care children's hospital from April to October 2019. Subjects: Our patient cohort included 24 pediatric patients ages ranging from birth to 19 years old with both cyanotic and acyanotic cardiac lesions. Interventions: Retrospective analyses of pediatric blood specimens, as well as patient, bypass, and postoperative data, were performed. Measurements and Main Results: We observed a statistically significant increase in soluble MER concentration post cardiac bypass in 17 of 24 patients (71%). Conclusions: Soluble MER concentrations increase with cardiopulmonary bypass–induced inflammation and myocardial ischemia and reperfusion injury in pediatric patients. The utility of soluble MER as a clinical biomarker to identify pediatric patients at risk for exacerbated postoperative outcomes after bypass-induced myocardial ischemia and reperfusion injury requires further investigation. Abstract : Supplemental Digital Content is available in the text.